The Courtyard site at Rødskjær - Cerbing, Mikael (Tromura, 2025)
During excavations performed by The Arctic University Museum in 2023, a courtyard site with an associated cooking pit field was discovered at Rødskjær.The cooking pit field consisted of over 155 cooking pits spread across an area of more than 3,500 m², beyond the boundaries of the excavation site. The oldest pits were dug during the late Pre-Roman Iron Age, while the youngest dated to the early Viking Age, with the majority of the pits dated to between AD 100 and 500.The courtyard site consisted of at least 16 houses, most of which were multi-phased. The houses appeared to be relatively similar in design overall. They were small three-aisled longhouses, approximately 11 meters in length and 4 meters in width. All the houses seemed to have had multiple hearths, but only two of the houses contained other types of structures, both of which featured oven installations. The activity phase of the courtyard site is estimated to have been between approximately AD 250 and sometime in the late 6th century or early 7th century, although traces of scattered, later activity were also found.Very few artifacts were discovered at the site, and most of what was found was located in the topsoil. However, a large quantity of bones was collected, primarily from sheep/goats and some cattle. It is likely that these animals were slaughtered at the site.A significant number of scientific samples were collected during the excavation. These included a large number of C14 samples, macrofossils, phosphate, and sedaDNA, all of which have been analyzed and are included in the accompanying report.
Keywords: archaeology; Archaeological excavation; Early Iron Age; Late Iron Age; Roman Period; Migration Period; Merovingian Period; Courtyard site; Court site; Cooking pit; Cooking pit field; Oven